Strategi Komunikasi Pemasaran Wapple.Id Dalam Meningkatkan Kepercayaan Konsumen - Muhammad, Alfarizi; Oxcygentri, Oky; Ema, Ema (Innovative: Journal Of Social Science Research, 2024)
The development of the modern era has significantly influenced various aspects, particularly in technology, transportation, and production. This phenomenon has also created a demand for mobile phone service providers as a solution for consumers facing issues with their electronic devices. Wapple.id, an iPhone service store in Karawang, responds to this need by developing an effective marketing communication strategy to enhance consumer trust.Wapple.id specializes in repairing Apple products, offering repair services for various devices such as iPhones, iPads, MacBooks, and Apple Watches since 2020. Wapple.id's marketing strategy involves utilizing social media, with Instagram being the primary platform. They leverage Instagram Ads and engage with local accounts to reach their target market, especially the millennial generation who are iPhone users in Karawang. Additionally, Wapple.id actively participates in music events in Karawang as a unique promotional method.This research adopts a qualitative approach, focusing on Wapple.id marketing communication strategy and its impact on consumer trust. The results indicate that the integration of Publicity and Public Relation, Event Experience, and Direct Marketing within the framework of Integrated Marketing Communication (IMC) successfully strengthens brand presence and increases consumer trust.